Influence of religiosity and studying law on college students' punitive attitudes in China. (February 2022) - Chu, Doris C; Cretacci, Michael A; Gao, Yandong
A number of studies in the United States examine the impact of religiosity on attitudes towards various types of criminal sanctioning. Research seems to indicate that more conservative denominations and faiths have a more punitive preference for criminal sanctions. Previous studies have also examined these attitudes between criminal justice and non-criminal justice students. While this area of inquiry has drawn attention in the United States, only scant attention has been paid to this phenomenon in other countries. To the best of our knowledge, no study has addressed this issue in China and our research seeks to serve as a foundation for examining this topic in that country. Using data collected from students attending universities in China, we examine the relationship between respondents' religiosity and their punitive attitudes. We also compare the punitive attitudes between law and non-law majors. Findings indicate that students with higher levels of religious behaviour were less likely to support the death penalty. In addition, law majors were found to be less likely to endorse severe sentences. Suggestions for future research are discussed.